Analisis Faktor-faktor yang Mempengaruhi Kinera Pegawai dalam Pegawai Organisasi Sektor Publik - Victorinus Laoli (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2019)
The purpose of this research was examining the factors that affect the employee performance at the tax office in Gunungsitoli. The factors tested in this study were clear and measurable goals, incentives, motivation, remuneration, decentralization, and performance measurement systems for employee performance. This research was conducted by using questionnaires to all employees of Kantor Penyuluhan Dan Konsultasi Perpajakan KP2KP Gunungsitoli. The data obtained was processed by using a regression that is part of the multiple regression. Number of questionnaires processed amounted to 40 questionnaires. The results of this study indicate that a clear and measurable goals, incentives, motivation, remuneration, decentralization is not related to employee performance. While performance measurement system affect employee performance.